Integriti dalam kalangan pekerja awam: kajian kes Agensi Keselamatan Sempadan (AKSEM) Chuping, Perlis - Ahmad Syamil, Abu Bakar (2019)
The main aim of this study is to examine integrity among civil servants in Malaysia. In order to achieve this, the research has selected a case study of the Border Security Agency (AKSEM) in Chuping, Perlis by focusing on the level of knowledge and integrity practices as well as on the factors that affect the deterioration of the integrity among civil servants in this agency. This study also analysed relations between demographic information such as gender, age, race, education status, service period (only for AKSEM civil servants only) and level of integrity. The study involved 30 respondents comprising 20 civil servants from AKSEM Chuping, Perlis. All the respondents had been interviewed to examine the level of knowledge and integrity practices as well as on the factors that affect the deterioration of the integrity among civil servants in this agency. The results show that the level of knowledge regarding integrity can affect the level of their integrity practices. Besides that, this study also highlights the factors that affect the decline of integrity among civil servants and provide some effective proposals in addressing the issues. All parties should play their roles in ensuring successfulness of programmes initiated by the government in enhancing level of integrity comprehensively. However, for a more comprehensive outcome, thorough analysis and adequate timeframes need to be implemented to address the problematic factors that cause higher probability of diminishing integrity among Malaysians, especially among those civil servants who serve as mediators between people and the government. If these civil servants have not possessed good integrity values, this will have negative impact on the image of government administration.